Kiss Good Night - Hest, Amy; Jeram, Anita (Cambridge, MA : Candlewick Press, 2001)
Even after a story, being tucked in, and warm milk, Sam is not ready to go to sleep until his mother kisses him good-night.
Accelerated Reader AR